Desain Metode Penanganan Pengaruh Iklim Organisasi terhadap Kepuasan Kerja Dokter di Komunitas Profesional Kesehatan - Muhammad Faridz Syahrian; Santy Deasy Siregar; Indra Gunawan; Devi Novando; Devi Nurhayati (Jurnal Mitra Prima, 2025)
Purpose: This community service activity aims to improve the performance of the immunization program through strengthening leader behaviors and management processes at Puskesmas Pujud. Design/methods/approach: This activity used a descriptive approach through community service implementation. Data were collected using observation, interviews, questionnaires, and documentation. The intervention included counseling, training, and mentoring for health workers. A total of 20 participants were involved. Findings/results: The results showed an improvement in participants’ understanding of leadership and management concepts. Team coordination improved, particularly in task distribution and communication. The implementation of management functions became more structured, especially in planning, implementation, and supervision. Furthermore, the performance of the immunization program improved, indicated by increased immunization coverage, timely implementation, and improved recording and reporting systems. Conclusions: Community service activities focusing on strengthening leadership and management processes can effectively improve the effectiveness of immunization programs at primary healthcare centers.